MENINGKATKAN KEMAMPUAN MENULIS TEKS NARRATIVE SURAT DINAS MELALUI MODEL PEMBELAJARAN MAKE A- MATCH - Siti Mutiah (LPPM STKIP PGRI Sidoarjo, 2022)
Mastery of good and correct Indonesian language skills is an absolute requirement that must be possessed in the current era of communication and globalization. Learning Indonesian, especially the ability to write official letters at the SMK level, is the main material as part of the function of developing students' skills in the fields of Science, technology and the arts. live in the future. The use of the make a match learning model can improve student learning activities. This can be proven by the percentage of student activity in the first cycle of learning activities. The average score is 71.2 with a percentage of less than 36%, enough 16%, and good at 48%. In the second cycle, corrective action was taken to learn, and the results were satisfactory, the activeness of students in participating in Indonesian lessons in writing narrative texts had increased. The average score is 81.6 with a percentage of less than 8%, just 4%, good 88%. The use of the make a match learning model can also improve student achievement in class XII AKL-1 SMK Negeri 1 Pamekasan in Writing Official Letter Narrative Texts. This can be proven through an evaluation/written test with an average student score in the first cycle of 67.2 with a learning mastery rate of 64%, increasing in cycle 2 to an average of 78.4 with a learning mastery level of 88%.An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.